The Effectiveness of Embedding Islamic Education on the View of the Meaning of Adolescents' Life in the Orphanage Environment in Padang Sidimpuan - Pane, Riem Malini; Ahman, Ahman; Nurihasan, Juntika (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this research was to get an overview of the meaning of life for orphanage adolescents in Indonesia. There have been several studies on the meaning of life conducted in any country, including Indonesia, but the use of religious counseling for teenagers, particularly those living in orphanages, is still limited. The tools used to measure the meaning of life are three values: creative values, experience values, and attitude values, which are translated into 30 items. This study uses a descriptive quantitative method, which is a method that describes the level of meaning in the lives of orphanage adolescents based on numerical data analysis. The results of the study showed that the 35 adolescents from the orphanage had general descriptions of: 1) a very high level of meaning in life that does not exist; 2) one of a high level (3%); 3). Seven of a moderate level (20%); 4). Eleven of a low level (31%); and 5). sixteen of a very low level (46%). These results indicate the importance of developing the meaning of life for orphanage youth through various efforts and interventions, especially in Indonesia.Keywords: Youth, Meaning of Life, Islamic Counseling.